2004
DOI: 10.1142/s0219633604000970
|View full text |Cite
|
Sign up to set email alerts
|

THE ϕ, ψ SPACE OF BORON ISOSTERES OF AMINO ACIDS: ANAB INITIOSTUDY

Abstract: Boron isosteres [ CH 3- CO - BH - CH(R) - CONHCH 3; R = CH 3, CH 2 OH , CH 2 SH ] of natural amino acids have been designed as inhibitors of serine protease based on boron's ability to mimic the transition state of the normal enzyme catalyzed reaction. The conformation and electronic properties of these isosteres have been determined by ab initio calculations at the HF/6-31G** level of theory. The global minimum energy structures of the boron isosteres (which are all identical) and the natural amino acids are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…This means that a nucleophilic attack by, say, the serine hydoxyl group in serine proteases, would occur preferentially at the boron atom than at the carbonyl group. This precisely was the basis of our original design of boron peptides as potential inhibitors of serine protease, as reported in our previous work [11]. However, with "ESP-fitted charges," the difference in the partial positive charge of boron and the carbonyl carbon is slightly less.…”
Section: Npamentioning
confidence: 64%
See 2 more Smart Citations
“…This means that a nucleophilic attack by, say, the serine hydoxyl group in serine proteases, would occur preferentially at the boron atom than at the carbonyl group. This precisely was the basis of our original design of boron peptides as potential inhibitors of serine protease, as reported in our previous work [11]. However, with "ESP-fitted charges," the difference in the partial positive charge of boron and the carbonyl carbon is slightly less.…”
Section: Npamentioning
confidence: 64%
“…This suggests that boron is actually "bonded" to four atoms rather than three, in the structures with ϭ 90°and 270°. The unique values of the angle (90°or 270°) assumed by boron peptides have a deep impact on the and angles that these peptides can adopt [11]. These differences can be used to design peptides with a specific stereochemistry and distinctive secondary structure.…”
Section: Nbo Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent paper, 15 we had studied hydroxy derivatives of boron (Figure 1, 2B) which are counterparts of the N-hydroxy derivatives of natural peptides (Figure 1, 2A). The acylhydroxyboranes (Figure 1, 2B) are more accessible synthetically than the acylboranes 13 (Figure 1, 1B) designed earlier.…”
Section: Introductionmentioning
confidence: 92%
“…7,8 We have reported in a series of papers the remarkable effects of the isosteric replacement of the C --O and N-H groups of peptides by boron, on the electronic properties, the geometry, and conformations of peptides. [9][10][11][12][13] The replacement of the N-H group by B-H causes a shift in the v torsion from 1808 in natural peptides to 908 in the boron isostere. It has been observed that modifying the B-H bond as B-OH and further as B-OCH 3 is able to induce a change in the conformation of the peptide backbone from a random coil-like state to a more ordered secondary structure.…”
Section: Introductionmentioning
confidence: 99%